Heparanase promotes glioma progression via enhancing CD24 expression. Issue 6 (14th May 2019) - Barash, Uri; Spyrou, Argyris; Liu, Pei; Vlodavsky, Euvgeni; Zhu, Chenchen; Luo, Juanjuan; Su, Dongsheng; Ilan, Neta; Forsberg‐Nilsson, Karin; Vlodavsky, Israel; Yang, Xiaojun
Abstract : Heparanase is an endo‐β‐d ‐glucuronidase that cleaves heparan sulfate (HS) side chains of heparan sulfate proteoglycans. Compelling evidence tie heparanase levels with all steps of tumor formation including tumor initiation, growth, metastasis and chemo‐resistance, likely involving augmentation of signaling pathways and gene transcription. In order to reveal the molecular mechanism(s) underlying the protumorigenic properties of heparanase, we established an inducible (Tet‐on) system in U87 human glioma cells and applied gene array methodology in order to identify genes associated with heparanase induction. We found that CD24, a mucin‐like cell adhesion protein, is consistently upregulated by heparanase and by heparanase splice variant devoid of enzymatic activity, whereas heparanase gene silencing was associated with decreased CD24 expression. This finding was further substantiated by a similar pattern of heparanase and CD24 immunostaining in glioma patients (Pearson's correlation; R  = 0.66, p  = 0.00001). Noteworthy, overexpression of CD24 stimulated glioma cell migration, invasion, colony formation in soft agar and tumor growth in mice suggesting that CD24 functions promote tumor growth. Likewise, anti‐CD24 neutralizing monoclonal antibody attenuated glioma tumor growth, and a similar inhibition was observed in mice treated with a neutralizing mAb directed against L1 cell adhesion molecule (L1CAM), a ligand for CD24. Importantly, significant shorter patient survival was found in heparanase‐high/CD24‐high tumors vs . heparanase‐high/CD24‐low tumors for both high‐grade and low‐grade glioma ( p  = 0.02). Our results thus uncover a novel heparanase–CD24–L1CAM axis that plays a significant role in glioma tumorigenesis. Abstract : What's new? The heparanase enzyme has been associated with carcinogenesis in many ways but how it affects glioma development remains unknown. Here, the authors find that heparanase overexpression enhances the expression of the mucin‐like cell adhesion protein CD24. CD24 promotes glioma growth while anti‐CD24 antibodies attenuate the growth of glioma xenografts, providing a molecular mechanism underlying the protumorigenic properties of heparanase in glioma.